The Economic Opportunity Cost of Capital for Canada - An Empirical Update - Glenn Jenkins; Chun-Yan Kuo (Queen's University, Department of Economics, 2007)
The social or economic discount rate is the threshold rate used to calculate the net present value of an investment project, a program, or a regulatory intervention to see whether the proposed expenditures are economically worthwhile to undertake. The size of the economic rate of discount has been a policy issue in Canada for many years. The debate has been primarily concerned with the empirical measurement of the economic opportunity cost of funds. The purpose of this paper is to reexamine and update the empirical estimation of what is the appropriate economic discount rate for Canada. The results suggest that estimates of the economic discount rate can range from 7.78 percent to 8.39 percent real. As a consequence, we conclude that for Canada an 8 percent real rate is an appropriate discount rate to use when calculating the economic net present value of the flows of economic benefits and costs over time.
Keywords: H43; 330; discount rates; opportunity cost; project evaluation; Investitionsrechnung; Diskontierung; Soziale Diskontrate; Opportunitätskosten; Kanada